Minat Berwirausaha Mahasiswa Universitas Bina Insani Ditinjau dari Faktor Pengetahuan Kewirausahaan, Media Sosial dan Digital Marketing: Exploring Entrepreneurial Interest Among Bina Insani University Students through Entrepreneurial Knowledge, Social Media, and Digital Marketing - Fajri, Defitriani; Widiawati, Kristiana (Anterior Jurnal, 2025)
Indonesia has an unemployment rate of 5.25% among university graduates and a low interest in university graduates who become entrepreneurs. This study explores how entrepreneurial knowledge, social media, and digital marketing affect entrepreneurial interest among Bina Insani University FEB students (2021-2023) who have taken entrepreneurship courses. Using a quantitative approach method with a probability sampling technique and a simple random sample of 200 respondents, the data were analyzed using SPSS 29. The results showed that all three variables significantly (p < 0.05) and positively influence entrepreneurial interest, with digital marketing as the most influential factor (β = 0.344). The findings highlight the need to strengthen and diversify entrepreneurship education at Bina Insani University, integrate digital marketing and social media, and encourage collaboration with the digital industry and government to build relevant entrepreneurial skills that align with the new era of digitalization.